Aluminum-Activated Malate Transporters Can Facilitate GABA Transport. Issue 5 (4th April 2018) - Ramesh, Sunita A.; Kamran, Muhammad; Sullivan, Wendy; Chirkova, Larissa; Okamoto, Mamoru; Degryse, Fien; McLaughlin, Michael; Gilliham, Matthew; Tyerman, Stephen D.
Abstract : GABA and malate interact with ALMTs to regulate each other's transport, suggesting a role for ALMTs, which transport both GABA and malate in planta, in communicating metabolic status. Abstract: Plant aluminum-activated malate transporters (ALMTs) are currently classified as anion channels; they are also known to be regulated by diverse signals, leading to a range of physiological responses. Gamma-aminobutyric acid (GABA) regulation of anion flux through ALMT proteins requires a specific amino acid motif in ALMTs that shares similarity with a GABA binding site in mammalian GABAA receptors. Here, we explore why TaALMT1 activation leads to a negative correlation between malate efflux and endogenous GABA concentrations ([GABA]i ) in both wheat ( Triticum aestivum ) root tips and in heterologous expression systems. We show that TaALMT1 activation reduces [GABA]i because TaALMT1 facilitates GABA efflux but GABA does not complex Al 3+ . TaALMT1 also leads to GABA transport into cells, demonstrated by a yeast complementation assay and via 14 C-GABA uptake into TaALMT1 -expressing Xenopus laevis oocytes; this was found to be a general feature of all ALMTs we examined. Mutation of the GABA motif (TaALMT1 F213C ) prevented both GABA influx and efflux, and resulted in no correlation between malate efflux and [GABA]i . We conclude that ALMTs are likely to act as both GABA and anion transporters in planta. GABA and malate appear to interact with ALMTs in a complex manner to regulate each other's transport, suggestive of a role for ALMTs in communicating metabolic status.